Literature Review: Readiness to Change at the University - Erlyani, Neka; Suhariadi, Fendy (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: The study of readiness to change in the context of the University is needed in a situation to prepare for the 4.0 industrial revolution at the University which demands preparation in facing the VUCA era. The university is also in danger of being disrupted if it does not immediately make changes and adjustments to its role in the world of education. therefore readiness for change is the key for organizations to respond quickly and successfully to change. Methods: review the literature with a literature search strategy through publish or perish (the keywords used are readiness to change, universities, tertiary institutions). Results: 96 journal articles were found in publish or perish (step 1). The author manually screened the titles for inclusion and exclusion criteria to obtain 15 articles (step 2). All articles were subjected to an abstract review for screening according to criteria. From the results of the final selection, 11 reviewed journal articles were obtained. Conclusion: Acceptance and readiness to change is an important part of the organization especially the University which requires immediate attention. Need to be open to changes made before preparing for change. Alignment of the organization's vision and mission with employees' personal needs to be created by communicating messages of change so that they tend to have a positive attitude towards organizational change. Besides, trust in management proved to be important in implementing strategic decisions and an important determinant of employee openness to change. Keywords: Readiness to Change, University, Campus